The Jurisprudence and Legal Review of the Effect of Promise Fulfillment in Sustainable Development of Islamic Community with Comparative Study - Delgoshamehr, Nasser Hasan; Hasanzadeh Dizaji, Ozra karim; Sirghani, Mohsen (Journal of History Culture and Art Research, 2017)
One of the problems in different countries including Iran is contracts breach and termination of securities contrary to the ethics. If this process is not resolved via trust and negotiation, two parties refer to legal courts and this increases the legal cases and costly operation, legal procedure, different social problems, property loss that are sold by paltry price in the bids and this is not compensated sometimes. This study evaluates promise fulfillment from jurisprudence and legal aspects and its effect is explained in the sustainable development of Islamic community. Also, promise fulfillment shows high level of human character and ignoring this element leads to loss and this is evaluated with a comparative evaluation in this study.